A borehole heat store in rock : pilot trials in Luleå and preliminary design of a full-scale installation - Andersson, Sören; Johansson, Alf; Nordell, Bo; Åbyhammar, Tomas (Luleå tekniska universitet, Arkitektur och vatten, 1983)
Godkänd; 1983; 20090119 (andbra)